Pengembangan Kompetensi Penyuluh Pertanian Berbasis Media Massa - Oos M Anwas (Badan Standar, Kurikulum, dan Asesmen Pendidikan, Kemendikbudristek, 2010)
This study aimed is to analyze the intensity of the use of mass media, the suitability of the substance of the mass media with the needs of extension education, and their effects on the competency of agricultural extension agents. The mass media mentioned in this study were newspapers, magazines, books, radio, television and the internet. This research was conducted by survey method on the paddy extension agent PNS within districts of Karawang and the vegetable extension agent government employee in the district of Garut, West Java. Samples were randomly taken as much as 170 people. The result of descriptive analysis showed that the intensity of mass media utilization was low. The intensity of particular mass media utilization especially newspapers, books, radio and the internet were in a very low category. Utilization of the magazine was in fair category. Only the intensity of television media utilization was in the high category, even though their substances were less in accordance with the needs of the extension education. The multiple regression analysis found that the mass media that influence the competency of agricultural extension agents was the magazine by which the substance was in accordance with the needs of extension education, accessible, and continuous. On the other hand the high intensity of television media utilization was potential to increase the competency of agricultural extension agents.Â ABSTRAKPenelitian ini bertujuan untuk menganalisis intensitas pemanfaatan media massa, kesesuaian substansi media massa dengan kebutuhan penyuluhan, dan pengaruhnya terhadap kompetensi penyuluh pertanian. Media massa yang dimaksudkan adalah koran, majalah, buku, radio, televisi, dan internet. Penelitian ini dilakukan dengan metode survai terhadap penyuluh pertanian PNS padi di kabupaten Karawang dan penyuluh sayuran di kabupaten Garut Provinsi Jawa Barat. Sampel diambil secara random sebanyak 170 orang. Hasil analisis deskriptif diketahui secara umum intensitas pemanfaatan media massa adalah rendah. Secara khusus intensitas pemanfaatan media: koran, buku, radio, dan internet dalam kategori sangat rendah. Pemanfaatan majalah dalam kategori sedang, dan hanya intensitas pemanfaatan media televisi dalam kategori tinggi walaupun substansinya kurang sesuai dengan kebutuhan penyuluhan. Melalui analisis regresi berganda diketahui bahwa media massa yang berpengaruh terhadap kompetensi penyuluh adalah majalah yang substansinya sesuai dengan kebutuhan penyuluhan, mudah diakses, dan dilakukan secara kontinyu. Di sisi lain, intensitas pemanfaatan media televisi yang tinggi memiliki potensi sebagai media yang dapat digunakan untuk peningkatan kompetensi penyuluh.